2013
DOI: 10.1121/1.4805830
|View full text |Cite
|
Sign up to set email alerts
|

Build-up of auditory stream segregation induced by tone sequences of constant or alternating frequency and the resetting effects of single deviants

Abstract: Three experiments investigated the dynamics of auditory stream segregation. Experiment 1 used a 2.0-s constant-frequency inducer (10 repetitions of a low-frequency pure tone) to promote segregation in a subsequent, 1.2-s test sequence of alternating low- and high-frequency tones. Replacing the final inducer tone with silence reduced reported test-sequence segregation substantially. This reduction did not occur when either the 4th or 7th inducer was replaced with silence. This suggests that a change at the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Subsequent studies have shown that breakdown can also result from other changes, such as the relative delay between source and echo (Clifton et al,1994), and changes to source/echo spectral characteristics (McCall et al, 1998). It has also been shown with auditory streaming that sudden changes in the stimulus presentation can cause a resetting, or breakdown, of the buildup of segregation (Haywood and Roberts, 2013;Roberts et al, 2008;Bregman, 1993, 1998). To the extent that room exposure effects on speech understanding are related to the precedence effect and/or auditory object formation/streaming, one might expect to find similar evidence of breakdown following abrupt changes to the room acoustic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have shown that breakdown can also result from other changes, such as the relative delay between source and echo (Clifton et al,1994), and changes to source/echo spectral characteristics (McCall et al, 1998). It has also been shown with auditory streaming that sudden changes in the stimulus presentation can cause a resetting, or breakdown, of the buildup of segregation (Haywood and Roberts, 2013;Roberts et al, 2008;Bregman, 1993, 1998). To the extent that room exposure effects on speech understanding are related to the precedence effect and/or auditory object formation/streaming, one might expect to find similar evidence of breakdown following abrupt changes to the room acoustic environment.…”
Section: Introductionmentioning
confidence: 99%
“…No difference was anticipated between the two base frequencies (0.5 kHz and 1 kHz) because both fell within the frequency range for which the ratio ∆f over base frequency at the border between one-and two-stream percepts is roughly constant (Miller and Heise, 1950). All conditions elicited broadly similar patterns of build-up-an initial phase (up to ~10-12 s) that was relatively fast followed by a slower phase (Anstis and Saida, 1985;Haywood and Roberts, 2013;Rajasingam et al, 2018). In general, an increase in ∆f tended to increase both the rate and final extent of build-up.…”
Section: B Results and Discussionmentioning
confidence: 93%
“…They were asked to avoid listening actively for either integration or segregation, but simply to report which of the two percepts they heard at that moment; on occasions when the percept was ambiguous, listeners were asked to report the more dominant (cf. Haywood and Roberts, 2013;Rajasingam et al, 2018). At the end of each trial, there was a 5-s pause before listeners could initiate the next trial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations